On interpretative activity : a Peircian approach to the interpretation of science, technology, and the arts - Boulting, Noel (Philosophy of history and culture ;, 2006)
Using the ideas of the American scientist and philosopher Charles Sanders Peirce, three conceptions of interpretation can be distinguished: the Iconic, the Indexical and the Intellective. This trichotomy is based on Peirce's use of his sign theory and his logic of scientific discovery. The Iconic captures what is valuable in itself for an individual interpreter as opposed to the Indexical which is available for public appreciation as an outcome beyond Interpretative activities. The Intellective extends the Iconic to include the interpretative activities of groups of interpreters employing appropriate methods of inquiry in a more rigorous and rational way. Such distinctions can be used in confronting certain problems in science, technology and the arts.